Difference Of Evaporation and Boiling for Heterogeneous Water Droplets in a High-Temperature Gas - Legros Jean Claude; Piskunov Maxim V.; Strizhak Pavel A. (MATEC Web of Conferences, 2015)
Experimental investigation of vapor formation was carried out on water droplets on fixed graphite substrate and heterogeneous droplets (containing solid single inclusions) when heating in high-temperature gas. High-speed video shooting (up to 105 frames per second), optical method (Particle Image Velocimetry) and TEMA Automotive software were used. We revealed two phase change mechanisms of heterogeneous liquid droplets. Effect of evaporation and boiling on evaporation times of water droplets was determined.